Serum and urinary essential trace elements in association with major depressive disorders: a case–control study - Fu, Jiyong; Wang, Qinqin; Wang, Na; Li, Shilong; Zhang, Hongwei; Zhu, Yuxing; Guo, Hua; Wang, Fukun; He, Lei; Xia, Shuang; Cao, Bing (Frontiers in Psychiatry, 2023)
The etiology and pathophysiology of major depressive disorders (MDD) remain unclear. Increasing evidence has demonstrated that essential trace elements (ETEs) such as iodine (I), zinc (Zn), copper (Cu), selenium (Se), cobalt (Co), and molybdenum (Mo) play vital roles in MDD. In total, 72 MDD cases and 75 healthy controls (HCs) in the Zhumadian Second People’s Hospital, Henan Province, China were recruited in our study. The levels of different ETEs were examined in serum and urine, using an inductively coupled plasma mass spectrometer (ICP-MS), in both the MDD cases and HCs. Serum levels of I, Se, Cu, and Mo were significantly lower in the MDD cases than in the HCs (p<0.05), and urinary levels of I and Zn were significantly higher in the MDD cases than in the HCs (p<0.05). The serum concentration of I (Q3: OR = 0.210, Q4: OR= 0.272) was negatively associated with MDD after adjusting for potential confounders, including age, gender, and BMI; that urinary concentration of I (Q4: OR = 2.952) was positively associated. The higher levels of I, Se, Cu, and Mo in serum might be protective against the development of MDD, and the excess I and Zn in urine may be associated with MDD pathogenesis. Future research needs to gain a deeper understanding of the metabolic pathways of ETEs, especially I, Se, Zn, Cu, and Mo in MDD, and to understand the role of ETEs in the pathogenesis of depression.